Complementary Therapies - Bernardo-Filho, Mario; Taiar, Redha; da Cunha de Sá-Caputo, Danúbia; Seixas, Adérito (IntechOpen, 2022)
Traditional, complementary, and integrative medicine are terms used to try to define practices in the maintenance of health as well as in the prevention, diagnosis, and management of physical and mental conditions. These practices are based on the knowledge, skill, theories, beliefs, and experiences acquired by different cultures in the world throughout the years. This book presents a comprehensive overview of the qualities and applications of complementary therapies. It includes thirteen chapters in four sections: "Complementary Therapies and Knowledge of Some Cultural Practices," "Complementary Therapies and Mental Disorders," "Complementary Therapies and Clinical Rehabilitation," and "Complementary Therapies, Technologic and Science Perspectives."